Synthesis and characterization of Ag doped TiO2 heterojunction films and their photocatalytic performances - DEMİRCİ, SELİM (ELSEVIER, 2016)
In this study, undoped and silver (Ag) doped titanium dioxide (TiO2) films were successfully synthesized by sol-gel spin coating technique on the Si substrates. Photocatalytic activities of the TiO2 films with different Ag content were investigated for the degradation of methylene blue (MB) under UV light irradiation. The crystal phase structure, surface morphology, chemical and optical properties of Ag-doped TiO2 films were characterized using an X-ray diffractometer (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), UV-vis spectrophotometer, and FTIR spectrophotometer. The results showed that the Ag-doped TiO2 films calcined at 500 degrees C had the crystalline anatase phases and the surface morphologies with some cracks. Ag substitution into TiO2 matrix enhanced the photocatalytic activity of TiO2 films under UV light irradiation as compared to the undoped TiO2 film. Furthermore, the results indicated that the 0.7% Ag doped TiO2 film exhibited a superior photocatalytic activity than that of undoped and other Ag-doped TiO2 films. This study demonstrated the potential of an application of Ag doped films to efficiently treat dissolved organic contaminants in water. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Titanium dioxide; Silver; Photocatalytic activity; Methylene blue (MB); Hydrophilicity; SEMICONDUCTING METAL-OXIDES; THIN-FILMS; TITANIA FILMS; DEGRADATION; ANTIBACTERIAL; NANOPARTICLES; FABRICATION; DEPOSITION; RUTILE; DISINFECTION